Peran Kepemimpinan Kepala Sekolah dalam Mengembangkan Budaya Berprestasi di SD Negeri 3 Kandis Kecamatan Kandis - Mutmainah Mutmainah; Yasir Arafat; Hery Setiyo Nugroho (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to describe the role of principal leadership in developing a culture of achievement in State Elementary School 3 Kandis, Kandis District. Data collection tools used interview methods, documentation, observation and literature review. Data analysis used descriptive qualitative analysis with the stages of collecting data, data reduction, data presentation and drawing conclusions. The results of the study stated that the role of the principal in developing a culture of achievement in State Elementary School 3 Kandis, Kandis District 1) planning a program to develop a culture of achievement and school competitiveness both in the short and long term; 2) determining the planned program in the form of activity instruments; and 3) implementing programs that have been set by the school. In its implementation, there are internal obstacles faced by the principal in an effort to develop a culture of achievement at SD Negeri 3 Kandis, namely improving the quality of learning and teacher competence. There are several solutions that can be taken to overcome the obstacles faced in developing a culture of achievement through the quality of learning at SD Negeri 3 Kandis, including by supervising teachers, involving teachers in training activities, education and training, workshops, socialization, training, and KKG activities for teachers.